Diastereo‐ and Enantioselective Propargylation of 5H‐Thiazol‐4‐ones and 5H‐Oxazol‐4‐ones as Enabled by Cu/Zn and Cu/Ti Catalysis. Issue 46 (24th October 2018) - Fu, Zhengyan; Deng, Ning; Su, Sheng‐Nan; Li, Hongyang; Li, Ren‐Zhe; Zhang, Xia; Liu, Jie; Niu, Dawen
Abstract: Reported is the asymmetric propargylic substitution (APS) reaction of 5 H ‐thiazol‐4‐ones using a Cu/Zn dual metal catalytic system and the APS reaction of 5 H ‐oxazol‐4‐ones using a Cu/Ti catalytic system. These reactions furnish functional‐group‐rich, terminal‐alkyne‐containing products with two vicinal stereocenters in high yields and with good to excellent diastereo‐ and enantioselectivities. This study demonstrates the use of dual metal catalytic systems as a viable approach to improve the selectivity profiles of the copper‐catalyzed APS reactions. Abstract : 'CuTi' pie : Cu/Zn and Cu/Ti dual metal systems have been devised to achieve the highly diastereo‐ and enantioselective propargylic substitution of 5 H ‐thiazol‐4‐ones and 5 H ‐oxazol‐4‐ones, respectively. These reactions demonstrate substantial substrate scope, giving terminal‐alkyne‐containing, functional‐group‐rich products in high yields.